2012
DOI: 10.1017/s2040174412000335
|View full text |Cite
|
Sign up to set email alerts
|

Rate and pattern of weight gain in Indian women from the upper income group during pregnancy and its effect on pregnancy outcome

Abstract: Maternal weight gain and pattern of weight gain during pregnancy influence the ultimate outcome of pregnancy. Pregravid body mass index (BMI), maternal dietary intake, maternal height and age all determine the weight gain during pregnancy. The study was taken up with an objective to observe maternal weight gain and its pattern in pregnancy in women from an upper income group and to find out their association with pregnancy outcome. 180 normal primiparous pregnant Indian women (20-35 years) from an upper income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast, Nyaruhucha et al present evidence that weight gain in the third trimester but not in the second trimester is positively associated with birth weight [ 9 ]. Raje and Ghugre have demonstrated that weight gain in the third trimester is substantially correlated with the birth weight of the infant irrespective of maternal nutritional status [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Nyaruhucha et al present evidence that weight gain in the third trimester but not in the second trimester is positively associated with birth weight [ 9 ]. Raje and Ghugre have demonstrated that weight gain in the third trimester is substantially correlated with the birth weight of the infant irrespective of maternal nutritional status [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal weight gain in pregnancy and its pattern in different trimesters influence the outcomes of pregnancy [1]. Excessive weight gain during pregnancy (with incidence about 50%) has a significant impact on fetal growth and weight change in next generations [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…17 Raje et al in their study suggested higher income group had association with birth weight were mothers gained weight throughout the pregnancy and babies were heavier. 18…”
Section: Resultsmentioning
confidence: 99%